Wpływ składowiska odpadów górniczych "Smolnica" w Trachach na jakość wód powierzchniowych i podziemnych = Impact of Smolnica mining waste landfill in Trachy on the quality of surface and underground water in its surroundings - Czajkowska, Aleksandra; Gawor, Łukasz; Cieślok, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Incorrect location and exploitation of landfills negatively affect the environment, including the environment of surface water and underground water. The degree of onerousness of the landfill depends on the chemical and mineral composition of deposited wastes, and also construction, storage technology and geological, hydrogeological, hydrological, and location of landfill. In the article the impact of Smolnica mining waste landfill on the water environment was considered. Quality of surface and underground water, and also leachate was assessed on the basis of monitoring studies covering the period from 2004 to 2015 year (surface water and leachate) and period from 2009 to 2015 year (underground water).
Keywords: składowisko odpadów górniczych; wskaźniki zanieczyszczenia wody; wody powierzchniowe; wody podziemne; jakość wód; mining waste landfill; indicators of water pollution; surface water; underground water; water quality